Enhancing the students' skill in writing a narrative text using peer-editing - Satrio Ardi Nugroho (LPPM Universitas Bina Sarana Informatika, 2021)
The aims of this research were: 1) to identify whether peer-editing can enhance the students’ skill in writing a narrative text and 2) to describe the situation of the classroom when peer-editing technique is implemented. The method research used was classroom action research which consisted of two cycle. Each cycle consisted of planning, acting, observing, and reflecting. The research subject was the students of grade XI Bahasa dan Budaya of an SMA in Kudus in the academic year of 2019/2020. It comprised of 35 students with 12 boys and 23 girls. The qualitative data were collected by observation, questionnaire, and interview. The quantitative data were collected by conducting tests. The qualitative data were analyzed by condensing the data, displaying the data, and drawing conclusion. The quantitative data were analyzed by comparing the mean score of the students’ pre-test, post-test 1, and post-test 2. The result of the research showed that there were improvements on the students’ skill in writing a narrative text when peer-editing technique is implemented.Keywords: writing narrative text, peer-editing, classroom action research.